Supporting sustainable livestock value chains to restore large rangelands - Abiy, Rahel; Spinelli, Madison (2024)
The Sustainable Investments for Large-Scale Rangeland Restoration (STELARR) project aims to unlock private sector finance for rangeland improvement and restoration through sustainable livestock value chains. Launched in late 2023, the project is funded by the Global Environment Facility (GEF), and is being implemented by IUCN and executed by ILRI in partnership with the Alliance of Bioversity International and CIAT, International Center for Agricultural Research for Dry Areas (ICARDA), Center for International Forest Research and World Agroforestry (CIFOR-ICRAF), and the Sustainable Fibre Alliance.